2018
DOI: 10.1021/acsnano.7b07699
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Shaping of Femtoliter Dew Droplets

Abstract: Herein, we show that wetting properties such as giant wetting anisotropy and dynamic shaping can be observed when femtoliter (submicron scale) dew droplets are condensed on nanopatterned mildly hydrophilic surfaces. Large-scale, optically transparent, nanopatterned TiO surfaces were fabricated by direct nanoimprinting lithography of sol-gel-derived films. Square, infinitely elongated, or circular droplets were obtained with square, line, or concentric patterns, respectively, and were visualized in situ during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Beyond simple micro- and nanograting with homogeneous depths, nanopatterns having variable depths and dimensions within a single substrate zone may be capitalized in many applications requiring tunable optical, mechanical, and/or physicochemical characteristics, such as holograms, color filters, microfluidic platforms, , biosensors, photonic structures, , and electrochemical devices. Typical fabrication methods involving simple lithography and/or normal NIL, however, cannot easily produce such structures without resorting to time-consuming and costly procedures. By controlling the mold–substrate alignment angle and inscribing stroke direction, DNI enables tailored nanopatterning with gradient depth profiles and multidimensional structures in a continuous and very practical fashion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond simple micro- and nanograting with homogeneous depths, nanopatterns having variable depths and dimensions within a single substrate zone may be capitalized in many applications requiring tunable optical, mechanical, and/or physicochemical characteristics, such as holograms, color filters, microfluidic platforms, , biosensors, photonic structures, , and electrochemical devices. Typical fabrication methods involving simple lithography and/or normal NIL, however, cannot easily produce such structures without resorting to time-consuming and costly procedures. By controlling the mold–substrate alignment angle and inscribing stroke direction, DNI enables tailored nanopatterning with gradient depth profiles and multidimensional structures in a continuous and very practical fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Tailored Nanopatterning with Gradient Profiles and Multidimensions by Controlling the Mold Alignment Angle and Inscribing Stroke Direction. Beyond simple micro-and nanograting with homogeneous depths, nanopatterns having variable depths and dimensions within a single substrate zone may be capitalized in many applications requiring tunable optical, mechanical, and/or physicochemical characteristics, such as holograms, 37 color filters, 38−40 microfluidic platforms, 41,42 biosensors, 43−45 photonic structures, 46,47 and electrochemical devices. 48−50 Typical fabrication methods involving simple lithography and/or normal NIL, however, cannot easily produce such structures without resorting to time-consuming and costly procedures.…”
Section: Resultsmentioning
confidence: 99%
“…55 The deposition of a too-thick initial layer led to the presence of a 200 nm-thick residual layer. The same authors reproduced this method to elaborate patterned surfaces for controlled wetting 56 and 250 nm TiO 2 dielectric Mie resonator pillar arrays (aspect ratio 1) 57 with a residual layer as thin as 10 nm by applying a thinner initial sol−gel layer (see Figure 13). Chen et al 58 reported the fabrication of ultrathin GaAs solar cells with a TiO 2 /Ag nanostructured back mirror using the same procedure.…”
Section: Thermal Nilmentioning
confidence: 99%
“…The imprinting process is pressure-less, does not require any imprinting equipment and can be realized on large scale. [35][36][37] Figure S1 in Supplementary Material displays the photo of a patterned sample of 4 cm 2 exhibiting areas with different iridescent colors characteristic of diffractive gratings with periodicities ranging from 400 to 1000 nm. These two effects have been investigated by in-situ spectroscopic ellipsometry on a plane film during the thermal treatment.…”
Section: Soft-nanoimprinting Lithographymentioning
confidence: 99%